Coronary Microvascular Dysfunction: Pathophysiology, Clinical Phenotypes, and Mechanism-Guided Diagnostic Strategies - Divyansh Sharma; Daniel Bishev; Shudipan Chakraborty; Michael V. DiCaro; Ryan Shao; KiBuom Lee; KaChon Lei; Omar Shah; Sanjay Malhotra; Chowdhury Ahsan (Journal of Cardiovascular Development and Disease, 2026)
Coronary microvascular dysfunction (CMD) is a prevalent and clinically important cause of myocardial ischemia across the spectrum of coronary artery disease, including patients with angina and nonobstructive coronary arteries, persistent symptoms after revascularization, and acute coronary syndromes. Despite its prognostic significance, CMD remains underrecognized due to the limitations of angiography-centered evaluation and the heterogeneity of underlying biological mechanisms. This review presents a physiology-based framework for the assessment of CMD, emphasizing the role of invasive coronary function testing in defining mechanistic endotypes and informing clinical interpretation. We summarize the biological foundations of CMD, including endothelial dysfunction, vascular smooth muscle hyperreactivity, structural remodeling of the microcirculation, and extravascular myocardial influences, and describe how these processes manifest as distinct but overlapping clinical phenotypes. Contemporary invasive physiologic tools—coronary flow reserve, index of microcirculatory resistance, and vasomotor testing with acetylcholine—are reviewed with a focus on their complementary roles in localizing disease within the coronary circulation. The clinical application of microvascular testing is discussed in both stable coronary syndromes and acute coronary syndromes, highlighting differences in diagnostic intent, prognostic implications, and therapeutic relevance. We distinguish chronic CMD in stable syndromes from post–myocardial infarction microvascular injury, in which invasive indices have primarily prognostic implications. By integrating coronary biology, invasive physiology, and clinical context, this review supports a shift from purely anatomic assessment toward a mechanism-based, physiology-driven approach to ischemic heart disease.